Determination of 20 Neonicotinoid Insecticides and Their Metabolites in Infant Foods by a Modified QuEChERS Method Combined with HPLC-MS/MS - Liqiang Guo; Kai Li; Jinling Zhang; Guoning Tian; Ke Wang; Yajing Li (Journal of Chemistry)
A rapid, effective, and reliable method for the simultaneous detection of 20 neonicotinoids and their metabolites in infant foods has been developed using liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). To improve the accuracy and precision of the method, different extraction solvents, extraction methods, and adsorbents were evaluated to achieve a better recovery and clean-up effect. Under optimized conditions, the samples were extracted with acetic acid acidified acetonitrile/ethyl acetate by ultrasonication, and then were cleaned with reduced graphene oxide@Fe3O4 (rGO@Fe3O4) and primary and secondary amine (PSA) through a QuEChERS step. A matrix-matched calibration method was applied for quantification. Relative standard deviations were all <15% for intraday and interday precision. The values of limit of detection and limit of quantification were ranging from 0.02–0.35 μg·kg−1 and 0.1–1.0 μg·kg−1, respectively. The presented method was applied to the analysis of real samples.